A compound structure and a single‐step identification procedure for I/Q and DC offset impairments and nonlinear distortion modeling and compensation in wireless transmitters. Issue 3 (5th October 2012) - Saffar, D.; Boulejfen, N.; Ghannouchi, F.M.; Helaoui, M.; Gharssalah, A.
Abstract The nonlinear behavior of power amplifiers (PAs) and the in‐phase/quadrature (I/Q) imbalance in I/Q modulators are considered as the main sources of distortions and impairments in radio frequency transmitters. In this article, a compound structure and a single‐step identification procedure are proposed for the modulator's I/Q imbalance and DC offset and the PAs nonlinearity modeling and compensation of wireless transmitters. In fact, the performance of the digital predistortion technique used for PA linearization is adversely affected by the I/Q modulator's impairments that result mainly from gain/phase imbalance and DC offset. The measurement results reveal the robustness of the proposed model in modeling and linearization of the PA in the presence of I/Q modulator imperfections and show its superiority as compared to the generalized memory polynomial model and the dual‐input polynomial model. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2013.